1992
DOI: 10.3109/17453679209154731
|View full text |Cite
|
Sign up to set email alerts
|

Hip arthroplasty in Jutland, Denmark

Abstract: During the 10-year period 1981-90, 1752 primary total hip arthroplasties were performed in the County of South Jutland, Denmark. The annual number increased to a steady state during 1988-90. In this period, the incidence was highest in the age group 70-79 years for both women and men, with 485 and 410 arthroplasties per 100,000 inhabitants, respectively; the overall incidence was 82 per 100,000 inhabitants. During the next 30 years, the demand for primary hip arthroplasties in Denmark is expected to increase b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The low number of operations in 1995 may be due to a long hospital strike in that year. Overgaard et al (1992) reported an incidence of Havelin et al (2000) reported a frequency of 120 THR/100,000 inhabitants/year. In Sweden, it has been calculated that the incidence per 100,000 inhabitants/year should be 130, in order to meet the need (Herberts and Malchau 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The low number of operations in 1995 may be due to a long hospital strike in that year. Overgaard et al (1992) reported an incidence of Havelin et al (2000) reported a frequency of 120 THR/100,000 inhabitants/year. In Sweden, it has been calculated that the incidence per 100,000 inhabitants/year should be 130, in order to meet the need (Herberts and Malchau 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Above 500,000 joints are replaced each year in the USA alone, and thousands of patients have this procedure every year globally [1]. The average demand for complete implants is anticipated to rise by almost 30 % over the next decade and a half [2]. There will be an increase from 10.1 million to 13.9 million people living with osteoporosis between 2002 and 2020 [3].…”
Section: Introductionmentioning
confidence: 99%